Penerapan Nilai Birrul Walidain dalam Kehidupan Remaja Sehari-hari di Dusun Kemangunan Desa Bumiharjo Kecamatan Klirong - Rahmadhani, Laely; Kurniawan, Benny (IAINU Kebumen, 2025)
This study aims to analyze the application of the values ​​of birrul walidain in the daily lives of adolescents in Kemangunan Hamlet, Bumiharjo Village, Klirong District. The study used a descriptive qualitative method with a case study approach. Informants consisted of four adolescents aged 12-15, four parents, and two community leaders. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The results indicate that the values ​​of birrul walidain have begun to be internalized in adolescents' lives, reflected in politeness, obedience, responsibility, and respect for parents. Implementation is influenced by internal factors, such as religious motivation, religious understanding, and mobile phone use, as well as external factors, including parental role models, support from community leaders, and peer influence. This study emphasizes the important role of the family and social environment in supporting the implementation of these values ​​in adolescents.